Association between the Brazilian Breastfeeding Network implementation and breastfeeding indicators - Danusa S. Brandão; Sonia I. Venancio; Elsa R.J. Giugliani (Brazilian Society of Pediatrics, 2015)
Objective: To estimate the association between the implementation of the Brazilian Breastfeeding Network and prevalence of breastfeeding in a medium‐size city in southern Brazil. Methods: This was a cross‐sectional study involving 405 children under 1 year who participated in the second phase of the multivaccination campaign in 2012. Children's consumption of food on the day before the interview was obtained through interviews with mothers or guardians. The manager and one health professional from every health facility that joined the Network were interviewed in order to investigate the process of implementation of this initiative. The association between prevalence of breastfeeding and exclusive breastfeeding and adherence to the Network implementation process was tested using Poisson regression with robust variance. Results: Multivariate analysis revealed that among the children assisted by health facilities who joined the Network and those attending services that did not adhere to this strategy, the prevalence of breastfeeding (74% and 70.4% among children under 1 year, respectively) and exclusive breastfeeding (43.3% and 38.1% among children under 6 months, respectively) did not differ significantly. Difficulties in implementing the Network, such as high turnover of professionals, not meeting the criteria for accreditation, and insufficient monitoring of the health facilities by the supervisors of the Network were identified. Conclusion: Contrary to the hypothesis of this study, there was no significant association between the implementation of the Brazilian Breastfeeding Network and prevalence of breastfeeding and exclusive breastfeeding in the studied city. It is possible that the difficulties found in implementing the Network in this city have influenced this result.